Efficiency versus equality in bargaining - Fabio Galeotti; Maria Montero; Anders Poulsen (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
We report experimental data from bargaining situations where bargainers can make proposals as often and whenever they want, and can communicate via written messages. We vary the set of feasible contracts, thereby allowing us to assess the focality of three properties of bargaining outcomes: equality, Pareto efficiency, and total earnings maximization. Our main findings are that subjects avoid an equal earnings contract if it is Pareto inefficient; a large proportion of bargaining pairs avoid equal and Pareto efficient contracts in favor of unequal and total earnings maximizing contracts, and this proportion increases when unequal contracts offer larger earnings to one of the players, even though this implies higher inequality. Finally, observed behavior violates the Independence of Irrelevant Alternatives axiom, a result we attribute to a "compromise effect".
Keywords: C70; C72; C92; 330; bargaining; efficiency; equality; communication; experiment; independence of irrelevant alternatives